Accretion and winds - Klare, Gerhard (Reviews in modern astronomy, 1990)
Some new elements in accretion disk theory / F. Meyer -- Mass transfer and evolution in close binaries / A.R. King -- Radiation hydrodynamics of the boundary layer of accretion disks in cataclysmic variables / W. Kley -- Curious observations of cataclysmic variables / F.V. Hessman -- Accretion in AM Herculis stars / A.D. Schwope -- X-ray diagnostics of accretion disks / G. Hasinger -- Accretion phenomena at neutron stars / A. Rebetzky ... [et al.] -- A torus-dynamo for magnetic fields in galaxies and accretion disks / D. Schmitt -- Winds from hot stars / S.P. Owocki -- Radiation driven winds of hot luminous stars : applications of stationary wind models / A.W.A. Pauldrach and J. Puls -- Theory of radiatively driven winds of hot stars : II. Some aspects of radiative transfer / J. Puls and A.W.A. Pauldrach -- Winds of late type stars / H.-P. Gail -- Analyses of Wolf-Rayet stars / W.-R. Hamann ... [et al.]
Literaturangaben
Keywords: Konferenzschrift -- 1990 -- Berlin; Sternwind; Akkretion